Use of Digital Cadastral Map in Land Information Systems. - Asadova Manzura Akhatovna; Khamraev Salahitdin Ataevich; K.M.Mukhamadov (Indonesian Journal of Innovation Studies, 2022)
This paper presents the problem of cadastral maps. The cadastre that existed until now, consisting of paper maps and land books, is now becoming insufficient. Its shortcomings cause developments leading to its improvement. One way is to create a Land Information System.